Larkin’s Poetics - Dósa, Attila (Hungarian Journal of English and American Studies, 2021)
Book review: Rácz, István. Philip Larkin’s Poetics: Theory and Practice of an English Post-War Poet. Leiden and Boston: Brill Rodopi. 2016. 235 pages. ISBN 978-90-04-31106-0. Hb. €76.00.